PENGEMBANGAN MEDIA PEMBELAJARAN EBOOK KENAMPAKAN ALAM DAN BUATAN PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) KELAS III SEKOLAH DASAR - Isaroh muchodimah; Wawan Priyanto; Mira Azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop digital learning media in the form of interactive Ebooks for natural and artificial features material in the subject of natural and social sciences (IPAS) for grade III Elementary School. The background of this study is the low understanding and participation of students due to the use of lecture methods and LKS without the support of interactive visual or digital media. The formulation of the research problem is 1) How is the product of the development of natural and artificial features Ebook learning media in natural and social sciences (IPAS) for grade III Elementary School. 2) How is the feasibility of natural and artificial features Ebook learning media in natural and social sciences (IPAS) for grade III Elementary School 3) How is the practicality of natural and artificial features Ebook learning media in natural and social sciences (IPAS) for grade III Elementary School. This study uses ADDIE Research and Development (R&D) research with five stages, namely analysis, design, development, implementation and evaluation. Media development was carried out using the Canva and Heyzine applications. The study was conducted at SDN Mranggen 2 with 30 grade 3A students. The data from this study were obtained from observations, interviews, and questionnaires. Validation by material experts, media experts, teacher response questionnaires, students. and Ebooks were designed with a composition of 70% visual and 30% text that was adjusted to the cognitive development stage of elementary school students. The results of the study showed that this learning media was suitable for use with an average score of 96% from media experts and 94% from material experts, and was stated to be practical based on teacher responses of 95% and students of 98.4%. From these scores, it was stated that the Ebook media was very valid and practical to use in the learning process in grade III of elementary school.